2018
DOI: 10.15421/011809
|View full text |Cite
|
Sign up to set email alerts
|

Ethno-botanical and geo-referenced profiling of medicinal plants of Nawagai Valley, District Buner (Pakistan)

Abstract: The prime objective of the research was to list the important ethnomedicinal plants of Nawagai village, District Buner. During the survey, 44 plant species from 27 families were observed and collected from the targeted area of Khyber Pakhtunkhwa, Pakistan. Lamiaceae members were the most dominant (54%) followed by members of Asteraceae (30%), Poaceae (18%) and Solanaceae (12%). Relevant information such as field data, GPS coordinates family names, local names, therapeutic uses and plant habits were recorded fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The comparison of our study with the ethnomedicinal literature indicated that neighboring areas [ 41 , 42 , 43 ], while the more distant areas had comparatively fewer similarities, due to cultural and traditional differences—thus, confirming our respective hypothesis. The comparative study between previously reported medicinal plants showed that six plant species, Aconitum violaceum, Broussonetia papyrifera, Cedrus deodara, Celtis caucasica, Conandrium arnotaimum, and Pinus wallichiana , were not previously documented in this area for their medicinal values.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The comparison of our study with the ethnomedicinal literature indicated that neighboring areas [ 41 , 42 , 43 ], while the more distant areas had comparatively fewer similarities, due to cultural and traditional differences—thus, confirming our respective hypothesis. The comparative study between previously reported medicinal plants showed that six plant species, Aconitum violaceum, Broussonetia papyrifera, Cedrus deodara, Celtis caucasica, Conandrium arnotaimum, and Pinus wallichiana , were not previously documented in this area for their medicinal values.…”
Section: Discussionsupporting
confidence: 85%
“…It lies between 34°09′ 34°43′ N and 72°10′ 72°47′ E, covering an area of 1760 km 2 ( Figure 1 ). The region is surrounded by Swat and Shangla to the North, by Malakand Agency to the west, by Mardan District to the south and by Hazara Division to the east [ 41 ]. The climate of the lower regions of the valley is sub-tropical, and the upper regions are temperate.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, during the introduction process for the further effective development of the collection of rare and introduced species of plants, more attention should be paid to the biomorphological, geographic and cenotic analysis of the studied species currently represented in collections of botanical gardens, in order to identify the most promising groups for further active use in landscaping on the basis of their features (Sokolov, 1957;Peregrym et al, 2014;Umair et al, 2017;Zaman et al, 2018;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The daily UV shocks also affect the plumule and radicle length of newly growing plant (Flint and Caldwell, 2003). High intensities of UV light are destructive to all organisms including microbes (Zaman et al, 2018;Barnes et al, 1993). Paul (2001) studied species and found that UV contacts can cause alterations physiologically, morphologically, and chemically and affect it molecularly.…”
mentioning
confidence: 99%